Do Developmental Dysplasia of the Hip Risk Factors Affect the Prognosis of Graf Type 2a Hip? - Karatekin, Yavuz Selim; Yalkın Çamurcu, İsmet (Cerrahpaşa Medical Journal, 2022)
Objective: Developmental dysplasia of the hip is usually asymptomatic in infancy. Detection of risk factors is important. The aim of this study was to determine the effect of known risk factors for worsening and transition to type 2b hip in patients with Graf type 2a. Methods: Patients diagnosed with Graf type 2a between 2014 and 2018 were analyzed retrospectively. Patients diagnosed with Graf type 2a dysplasia were divided into 2 groups as healed (group 1) and type 2b hips that needed treatment (group 2). Ninety-seven hips of 69 patients in group 1 and 75 hips of 50 patients in group 2 were evaluated. The groups were compared in terms of risk factors (gender, mode of delivery, family history, first birth, and fetal presentation) determined for developmental dysplasia of the hip. Results: One hundred seventy-two type 2a hips of 119 patients were evaluated. No significant difference was found between the groups in risk factors (gender, family history, first birth, mode of delivery, and fetal presentation) (P > .05). There was no significant difference between the groups in terms of initial alpha and beta angles (P > .05). The age of patients in group 1 at the time of diagnosis was significantly lower than that of group 2 (P = .026). Conclusion: We observed that various risk factors known to be effective in hip dysplasia were not effective in the transition from type 2a to type 2b. In addition, a lower rate of improvement can be expected in Graf type 2a hips approaching the third month compared to the patients in the early period. Cite this article as: Selim Karatekin Y, Yalkın Çamurcu İ. Do developmental dysplasia of the hip risk factors affect the prognosis of graf type 2a hip? Cerrahpaşa Med J. 2022;46(3):223-225.